Preparation and characterization of isoniazid and lamivudine co-loaded polymeric microspheres - Pandey G.; Yadav S.K.; Mishra B. (My University, 2025)
Context The rate of co-infection of HIV/Tuberculosis is increasing alarmingly. This calls for a drug delivery approach targeting both diseases. Objective The study aims to investigate co-loading of isoniazid, an antitubercular drug and lamivudine an antiretroviral drug, into polymeric microspheres for simultaneous treatment of both diseases. Materials and methods Microspheres were prepared by o/o emulsion solvent evaporation method by employing ethylcellulose and eudragit RS 100 as polymers. The prepared formulation was suitably characterized for FTIR, DSC, percent yield, loose surface crystals, entrapment efficiency, and in vitro studies. The surface morphology of microspheres was observed using digital microscope and scanning electron microscope. Cell viability study was done on Caco-2 cells. Results and discussion FTIR and DSC studies demonstrated compatibility and stability of excipients. Microscopy studies revealed that particles were spherical in shape and distributed over a range of 120–270 μm. Percent yield, LSC and %EE have shown promising results. In vitro release showed biphasic release pattern with sustained release up to 12 h. Mechanism of drug release followed Higuchi Kinetics and non-fickian release behaviour. The formulation containing drug/polymer ratio 1:2 and EU/EC of 1:1 showed optimum response in context to achievement of controlled release. The cell viability studies showed that the prepared system had no toxic effect on intestinal epithelial Caco-2 cells. Conclusion Polymeric microspheres were prepared and suitably characterized for simultaneous delivery of two drugs. This matrix system could be used for better therapeutic outcome in this deadly co-infection. © 2015 Taylor & Francis.